KINERJA PEGAWAI PERPUSTAKAAN KABUPATEN SAMPANG DALAM MELAYANI PELANGGAN - Rofiah, Rofiah; Tirta Firdaus, Sukma Umbara (Universitas Madura, 2017)
This study was conducted to determine the organization’s performance in the Library of Sampang District. This study uses the effectiveness theory of Mahmudi (2005), states that effectiveness is the relationship between the output with the goal. The greater the contribution of output to the achievement of objectives, the more effective the organization, program or activity. Effectiveness is the result of an inverse relationship between outcome an output.This study uses a qualitative method. Data source used primary data source and secondary data source. The data source consists of library staff and library visitors. Then the technique of data collection is done that is the technique of interview and documentation.The results showed that the organization’s performance in the Library of Sampang District, was declared ineffective because; 1) in the utilization level where from the large number of officers but they did not assist in the problem ofvisitors, 2) in the service coverage where the level of supply books with the needs of visitors are still lacking, and 3) in the satisfaction of visitors is still not maximized as well as less responsive officers, lack of knowledge of its duties and lack of awareness of its own employees bcome one important factor in achievening an effective organization.